Isolation of BPgp70, a fibroblast receptor for the envelope antigen of Rauscher murine leukemia virus. - Landen, B (1980)
A protein that avidly binds gp70, the envelope antigen of Rauscher murine leukemia virus (RMuLV), has been purified from the culture medium used for growth of BALB/c 3T3 mouse cells. Gel filtration chromatrography revealed the apparent Mr 10,000 BPgp70 was efficiently labeled when BALB/c 3T3 cells were grown in medium containing [3H]leucine, indicating a cellular origin for BPpg70. Metabolically labeled [3H]BPgp70 was not immunoprecipitated by IgG-anti RMuLV-gp&) alone, but was immunoprecipitated when gp70 was added, an indicaton of BPgp70 x gp70 complex formation. The dissociation constant estimated by immunoprecitipation agreed with the apparent Kd for binding of gp70 to BALB/c 3T3 cells. BPgp70 reversibly inhibited specific binding of 125I-labeled BMuLV-gp70 to BALB/c 3T3 cells when it was incubated with the 125I-labeled gp70 first. These data yielded a dissociation constant similar to that calculated from the immunoprecipitation data. 125I-Labeled BPgp70 also bound specifically to cells infected with RMuLV, but not to uninfected cells. Incubation of BALB/c 3T3 cells with the IgG fraction of an antiserum to BPgp70 inhibited the specific binding of 125I-labeled gp70 to these cells, but preimmune IgG did not. Complete inhibition was achieved at a less than 100:1 ratio of IgG anti-BPgp70 to gp70 binding sites.